2017
DOI: 10.3390/ijerph14121564
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Enhanced Photolysis of Norfloxacin: Kinetics, Matrix Effects, and Degradation Pathways

Abstract: Degradation of norfloxacin (NOR) was studied using a combination of microwave and UV irradiation methods (MW/UV process). Remarkable synergistic effect was found between MW and UV light. The removal rate with the MW/UV process was much faster than that with UV light irradiation only. Degradation of NOR followed second-order kinetics and ~72% of NOR could be removed in the first 5 min of MW/UV reaction. Influence of inorganic ions (cations (K+, Mg2+, Ca2+, Cu2+) and anions (Cl−, SO42−, NO3−, CO32−)), humic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The efficacy of the oxidant determines how well AOPs perform [45] . AOPs investigated for NRFX removal include photocatalysis [ 27 , [46] , [47] , [48] ], photolysis [ 49 , 50 ], chlorine processes [51] , [52] , [53] , ozonolysis [54] , [55] , [56] , sonolysis [57] , sonocatalysis [ 28 , 58 ], Fenton (sono-Fenton, electro-Fenton, and photo-Fenton, etc.) [ 25 , [59] , [60] , [61] , [62] ].…”
Section: Overview Of Nrfx Removal Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of the oxidant determines how well AOPs perform [45] . AOPs investigated for NRFX removal include photocatalysis [ 27 , [46] , [47] , [48] ], photolysis [ 49 , 50 ], chlorine processes [51] , [52] , [53] , ozonolysis [54] , [55] , [56] , sonolysis [57] , sonocatalysis [ 28 , 58 ], Fenton (sono-Fenton, electro-Fenton, and photo-Fenton, etc.) [ 25 , [59] , [60] , [61] , [62] ].…”
Section: Overview Of Nrfx Removal Methodsmentioning
confidence: 99%
“…[ 25 , [59] , [60] , [61] , [62] ]. The degradation of NRFX photolysis enhanced by microwave has been demonstrated by Liao, Sharma [49] . Within five minutes of the MW/UV reaction, approximately 75% of NRFX was removed.…”
Section: Overview Of Nrfx Removal Methodsmentioning
confidence: 99%
“…Studies have shown that an increase in the density of cations on the surface of mineral particles is beneficial to the microwave degradation of nitrosodiphenylamine, and the lower the free energy of cation hydration, the higher the degradation rate. This is due to the fact that hot spots can be formed by the selective heating of polar substances in mineral particles, including surface cations, hydroxide radicals, adsorbed water molecules and organic molecules (Liao et al 2017). Overall, all ions had little effects on MO degradation.…”
Section: Effects Of Ionsmentioning
confidence: 99%
“…Microwave irradiation has been tested to determine its efficacy for degrading pollutants because of its short reaction time, high effi and lack of secondary pollutant generation (Kim and Ahn 2017;Liao et al 2017a;Remya and Lin 2011a;Wang and Wang 2016). Additionally, the heating that occurs with microwave irradiation accelerates the reaction rates more than conventional heating, thereby saving energy and shortening the treatment process time (Liao et al 2017b).…”
Section: Introductionmentioning
confidence: 99%